Characterisation of the Hamamatsu photomultipliers for the KM3NeT Neutrino Telescope - Aiello, S.; Akrame, S. E.; Ameli, F.; Anassontzis, E. G.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aublin, J.; Avgitas, T.; Baars, M.; et al. (Journal of Instrumentation, 2018)
The Hamamatsu R12199-023-inch photomultiplier tube is the photodetector chosen for the first phase of the KM3NeT neutrino telescope. About 7000 photomultipliers have been characterised for dark count rate, timing spread and spurious pulses. The quantum efficiency, the gain and the peak-to-valley ratio have also been measured for a sub-sample in order to determine parameter values needed as input to numerical simulations of the detector.
Keywords: Cherenkov detectors; Large detector systems for particle and astroparticle physics; Neutrino detectors; Photon detectors for UV; visible and IR photons (vacuum)